Hg, Cd, As, and Pb in surface sediments from the tropical coastal lagoon Estero Salado, Gulf of Guayaquil-Ecuador - Ormaza-González, Franklin I.; Castro-Rendón, Rubén D.; Maridueña-Bravo, Ana; Bobadilla-Cordova, Nayiva; Ramos-Castañeda, Ivanna; Statham, Peter J. (Frontiers in Marine Science, 2024)
The Gulf of Guayaquil (GG) is the most important tropical estuarine system of the eastern coast of South America, receiving an average water flow of about 1 650 m3 s-1 from a river basin of approximately 33 700 km2. The city of Guayaquil surrounds the inner coastal lagoon of the Estero Salado (ES) that empties into the GG. This coastal lagoon is of high social, food production, and environmental importance for the city and the GG. However, there is limited high quality data on metal pollution in this zone, no recent information on Hg, and the extent to which sediment metal pollution extends into the GG is presently unknown. As, Cd, Pb, and Hg were analysed in surface sediments from the urban zone and gave average concentrations of 32.3, 2.08, 41.9, and 0.12 mg kg-1 (dry weight), respectively. Additionally, data were obtained for the first time for the El Morro Channel, south of the ES in the GG, which is expected to be a relatively pristine zone; average As, Cd, Pb and Hg concentrations were 6.6, 0.22, 7.9 and 0.02 mg kg-1 (dry weight), well below concentrations seen in the urban ES zone. Estimates of the geo-accumulation index for metal pollution, using the El Morro data as background values, were 1.7 (As), 2.7 (Cd), 1.8 (Pb) and 2.0 (Hg), making the ES class II and a moderately polluted estuary for As, Hg and Pb, but class III and “moderately to heavily polluted” for Cd. If the lowest concentrations of the EM samples are taken the ES is class III for As, IV for Hg and Pb, and V for Cd; id est, the ES would classify as a heavily to extremely polluted estuary regarding these metals. These data show the metal concentrations increase significantly as the main conurbation of Guayaquil is approached from offshore, indicating a strong anthropogenic source of metals from the city, with anticipated negative environmental impacts.